Entangled-photons generation with quantum dots - 李远;丁飞;Oliver G Schmidt (Chinese physics B, 2018)
Entanglement between particles is a crucial resource in quantum information processing, an important example of which is the exploitation of entangled photons in quantum communication protocols. Among the different available sources of entangled photons, semiconductor quantum dots （QDs） excel owing to their deterministic emission properties, potential for electrical injections, and direct compatibility with semiconductor manufacturing techniques. Despite the great promises, QD-based sources at＇e far from being ideal. In particular, such sources present several critical issues, which require the overcoming of challenges pertaining to spectral tunability, entanglement fidelity, photon indistinguishability and brightness. In this article, we will discuss the potential solutions to these problems and review the recent progress in the field.